Forebyggelse på tværs af det offentlige og private: Når patienter trodser myndiggørelse og efterspøger mere professionel involvering - Villadsen, Kaspar; Pii, Kathrine Hoffman (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
The article presents findings from an empirical study among patients and professionals involved in a preventive health program at a Danish hospital. It shows how patients enrolled in the program interact with health professionals in ways that challenge assumptions common to governmentality studies of prevention and health promotion. This literature has successfully explored how contemporary health promotion transgresses the public/private boundary by shaping the values of collectivities and individuals to fit better with public health objectives. By exploring the complex co-existence and intertwinements of discipline and biopolitics in preventive practices this study eschews an interpretation that views the powers of the professional health system as invasive and one-directional. Instead, the study demonstrates how patients in various ways defy a ‘patient-centered’ and empowering approach and demand to be treated medically and disciplined in a more traditional sense. The blurring of the public/private boundary, then, cannot be straightforwardly described as a result of a professional health system that, more or less subtly, reaches into the private lives of patients. A more complex picture emerges, as patients’ attitude reflect both traditional medicine and rationalities foreign to the health system.